2018
DOI: 10.1111/nmo.13313
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variant in the glucagon‐like peptide 1 receptor gene associated with greater effect of liraglutide and exenatide on gastric emptying: A pilot pharmacogenetics study

Abstract: The minor A allele of GLP1R (rs6923761) is associated with greater delay in GE T in response to liraglutide and exenatide. These studies provide data to plan pharmacogenetics testing of the hypothesis that GLP1R (rs6923761) influences weight loss in response to GLP1R agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 26 publications
0
45
0
2
Order By: Relevance
“…It should be noted though, that according to Chedid and colleagues, there was no statistically significant difference in weight loss between wild type and polymorphic allele carriers after exenatide and liraglutide treatment. Nevertheless, researchers have found prolonged gastric emptying half-life in GA / AA genotypes [ 112 ].…”
Section: Genes Associated With Dpp4-inhibitors and Glp1 Receptor Amentioning
confidence: 99%
“…It should be noted though, that according to Chedid and colleagues, there was no statistically significant difference in weight loss between wild type and polymorphic allele carriers after exenatide and liraglutide treatment. Nevertheless, researchers have found prolonged gastric emptying half-life in GA / AA genotypes [ 112 ].…”
Section: Genes Associated With Dpp4-inhibitors and Glp1 Receptor Amentioning
confidence: 99%
“…However, a further study in patients with poorly controlled T2DM found no statistical correlation between glp1r polymorphisms and GLP-1 responses [59]. Pharmacogenetic studies have additionally suggested a role for GLP-1R genetic variation in the extra-pancreatic effects of GLP-1RAs, including effects on gastric emptying [60] and cardiovascular safety of GLP-1RAs [61]. Selected glp1r SNPs have also been studied for changes associated with ligand-binding and signaling alterations [62].…”
Section: Polymorphisms Of the Glp1r Genementioning
confidence: 99%
“…The drug target gene GLP1R is the main focus in pharmacogenetic studies of GLP-1 receptor agonists. Some studies have shown that the carriers of the A allele in GLP1R rs6923761 have a propensity for a greater decrease in weight or a greater delay in GE after treatment with GLP-1 receptor agonists [88,89]. On the other hand, glycemic and weight response to exenatide have been consistently confirmed as an association with the GLP1R rs6923761 variant in overweight patients with T2D from China [90].…”
Section: Other Antidiabetic Agents and Associated Genesmentioning
confidence: 99%
“…However, another study indicates that GLP1R gene polymorphisms have no significant correlations with the response of treatment with GLP-1 analogue in patients with T2D [91]. In addition, the gene TCF7L2 rs7903146 variant also shows inconsistent results in pharmacogenetic studies of GLP-1 receptor agonists [88,92].…”
Section: Other Antidiabetic Agents and Associated Genesmentioning
confidence: 99%